2α-Methyl-5α-androstan-17β-ol-3-one-17β-heptanoate - Alexandru Turza; Marieta Muresan-Pop; Maria-Olimpia Miclaus; Gheorghe Borodi (Molbank)
Drostanolone is a popular synthetic dihydrotestosterone derivative and an anabolic–androgenic agent which belongs to the steroid class. The crystal structure of a new polymorph of the esterified prodrug of drostanolone, namely drostanolone enanthate, was elucidated using single crystal X-ray diffraction. Furthermore, it was analyzed using the thermal DTA/TGA technique and FT-IR spectroscopy.